Effect of AACVD processing parameters on the growth of Greenockite (CdS) thin films using a single-source cadmium Precursor - Ehsan, M.A.; Ming, H.N.; Misran, Misni; Arifin, Z.; Tiekink, E.R.T.; Safwan, A.P.; Ebadi, M.; Basirun, Wan Jefrey; Mazhar, M. (Wiley-VCH Verlag, 2012)
Greenockite (CdS) nanostructured thin films are deposited on soda and FTO conducting glass substrates by aerosol-assisted (AA)CVD using a single-source precursor bis-(N,N-dicylcohexyldithiocarbamato)(pyridine)cadmium(II), CdS 2CNCy 2 2.py (1), in pyridine, toluene, and THF solutions in the temperature range 350-450 Â°C. The precursor 1, characterized by physicochemical methods, undergoes facile thermal decomposition at 350 Â°C to give a stable residual mass of CdS. The thin films deposited from pyridine solution, and characterized by X-ray diffraction (XRD), UV-vis spectroscopy, field-emission scanning electron microscopy (FESEM), and energy dispersive X-ray (EDX) techniques, exhibit a band gap of 2.4 eV and a photocurrent density of 1.3 mA cm -2 at 0.4 V versus Ag/AgCl/3M KCl, suggesting their suitability for application in photoelectrochemical (PEC) cells.